2003
DOI: 10.1159/000074824
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Preeclampsia

Abstract: Endothelial dysfunction underlies the pathogenesis of preeclampsia, but its mechanism has not yet been completely understood. Elevated oxygen free radicals may partially explain the endothelial cell damage. In this study, we have aimed to measure homocysteine (Hcy) and nitric oxide (NO) levels as endothelial dysfunction markers in preeclamptic women. Nineteen preeclamptic (33.9 ± 1.4 weeks) and 15 gestational-age-matched normal pregnant women (35.5 ± 0.7 weeks) were included in the study. Mean NO level was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…In this study, significantly lower levels of NO were observed in the pre‐eclamptic women when compared with control group in accordance with the findings of Var et al 16 . However, Norris et al 17 .…”
Section: Discussionsupporting
confidence: 92%
“…In this study, significantly lower levels of NO were observed in the pre‐eclamptic women when compared with control group in accordance with the findings of Var et al 16 . However, Norris et al 17 .…”
Section: Discussionsupporting
confidence: 92%
“…This hypoperfusion induced ischaemic injury to hepatic cells and other organs cause increased release of intracellular LDH to circulation. [9][10][11][12][13][14][15][16][17] In the present study, increased serum LDH level in preeclamptic women than control women are attributed to these facts. Moreover, the progressively increased LDH level in severe preeclampsia indicates progression of cellular injury with severity of this disorder.…”
Section: Discussionmentioning
confidence: 82%
“…High levels of homocysteine are associated with higher risks of cardiovascular diseases (12). The mechanism is poorly understood, but high homocysteine levels seem to alter endothelial nitric oxide secretions, thereby inducing hypertension and ischemia (13). During a normal pregnancy, plasma homocysteine concentrations will decrease (5).…”
Section: Introductionmentioning
confidence: 99%